1996
DOI: 10.1007/bf02088179
|View full text |Cite
|
Sign up to set email alerts
|

On the role of glucocorticoid receptors in brain plasticity

Abstract: 1. The mapping of glucocorticoid receptors (GR) in the rat central nervous system (CNS) has demonstrated their widespread presence in large numbers of nerve and glial cell populations also outside the classical stress regions. 2. The present paper summarizes the evidence that glucocorticoids via GR in the CNS can act as lifelong organizing signals from development to aging. The following examples are given. (a) In the prepubertal and adult offspring, prenatal corticosterone treatment can produce long-lasting c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
14
2

Year Published

1998
1998
2011
2011

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(24 citation statements)
references
References 68 publications
8
14
2
Order By: Relevance
“…Unfortunately, the vast majority of studies on developmental effects of glucocorticoids concentrate on regimens and doses that lie well above those used in preterm labor, resulting in frank somatic effects and endocrine disruption (Bohn, 1984;Fuxe et al, 1994Fuxe et al, , 1996Gilad et al, 1998;Gould et al, 1997;Maccari et al, 2003;Matthews, 2000;Matthews et al, 2002;McEwen, 1992;Meaney et al, 1996;Weinstock, 2001;Welberg and Seckl, 2001). Accordingly, studies have reported both increases and decreases in locomotor and other general activities, likely a reflection of different dosing paradigms with varying degrees of persistent somatic growth impairment (Benesová and Pavlík, 1989;Ferguson and Holson, 1999;Flagel et al, 2002;Neal et al, 2004).…”
Section: Introductionsupporting
confidence: 40%
“…Unfortunately, the vast majority of studies on developmental effects of glucocorticoids concentrate on regimens and doses that lie well above those used in preterm labor, resulting in frank somatic effects and endocrine disruption (Bohn, 1984;Fuxe et al, 1994Fuxe et al, , 1996Gilad et al, 1998;Gould et al, 1997;Maccari et al, 2003;Matthews, 2000;Matthews et al, 2002;McEwen, 1992;Meaney et al, 1996;Weinstock, 2001;Welberg and Seckl, 2001). Accordingly, studies have reported both increases and decreases in locomotor and other general activities, likely a reflection of different dosing paradigms with varying degrees of persistent somatic growth impairment (Benesová and Pavlík, 1989;Ferguson and Holson, 1999;Flagel et al, 2002;Neal et al, 2004).…”
Section: Introductionsupporting
confidence: 40%
“…The adverse effects of glucocorticoids on brain development and behavioral outcomes have been well characterized but to date, most studies have focused on treatments that lie well above the dose range typical of therapeutic interventions in preterm infants, often sufficient to produce persistent stunting of somatic growth and outright cerebral atrophy and endocrine disruption (Bohn, 1984;Fuxe et al, 1994Fuxe et al, , 1996Gilad et al, 1998;Gould et al, 1997;Maccari et al, 2003;Matthews, 2000;Matthews et al, 2002;McEwen, 1992;Meaney et al, 1996;Weinstock, 2001;Welberg and Seckl, 2001). Models incorporating stress as a mechanism for increasing circulating glucocorticoids have also proven useful in characterizing neurodevelopmental defects, especially those influencing hypothalamus-pituitary-adrenal axis function (Dean et al, 2001;Felszeghy et al, 2000;Muneoka et al, 1997), but of course, these involve contributions of factors beyond glucocorticoids alone.…”
Section: Introductionmentioning
confidence: 43%
“…Our results reinforce the fact that brain development is among the processes most vulnerable to glucocorticoids, with disruption of cell acquisition and differentiation achieved at concentrations well below those required for therapeutic interventions. The demonstration of these actions in neural cell cultures, reproducing all the essential findings from glucocorticoid treatment in vivo (Bohn, 1984;Fuxe et al, 1994Fuxe et al, , 1996Gilad et al, 1998;Gould et al, 1997;Kreider et al, 2005aKreider et al, , b, 2006Maccari et al, 2003;Matthews, 2000;Matthews et al, 2002;McEwen, 1992;Meaney et al, 1996;Weinstock, 2001;Welberg and Seckl, 2001), indicates that disrupted neurodevelopment is a direct glucocorticoid effect, not secondary to growth impairment, neuroendocrine disruption or other confounding actions in the fetus, neonate or mother. The successful prevention of respiratory distress in tens of thousands of preterm infants annually in the USA needs to be balanced against the adverse effects on brain development in the hundreds of thousands of individuals that receive the treatment.…”
Section: Discussionmentioning
confidence: 70%
“…First, glucocorticoid use in preterm labor could contribute directly to adverse neurobehavioral outcomes, over and above the confounds of preterm delivery or of secondary effects on the maternalfetal unit, maternal-neonatal interactions, or maternal or offspring neuroendocrine function. Second, the wide window of vulnerability of neurodevelopment to disruption by DEX means that adverse effects, such as those already noted for glucocorticoid administration in vivo (Bohn, 1984;Fuxe et al, 1994Fuxe et al, , 1996Gilad et al, 1998;Gould et al, 1997;Kreider et al, 2005aKreider et al, , b, 2006Maccari et al, 2003;Matthews, 2000;Matthews et al, 2002;McEwen, 1992;Meaney et al, 1996;Weinstock, 2001;Welberg and Seckl, 2001), are likely to be exerted at any stage in the period of 24-34 weeks of gestation in which these agents are recommended for use (Gilstrap et al, 1995). Third, the targeting of multiple stages of neurodevelopment means that the net outcome will differ according to the maturational timetable for neurogenesis and differentiation in each brain region (Bayer et al, 1993).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation